A community of practice in a midwifery led unit. How the culture and environment shape the learning experience of student midwives. (July 2020) - Norris, Sarah; Murphy, Fiona
Abstract: Objective: To explore the teaching and learning experience of midwifery mentors and student midwives in a midwifery led unit. The aim of this paper is to discuss how a conceptual framework emerged from the findings of the study. Design and method: Ethnography. Non-participant observation of the daily work of an alongside midwifery led unit (AMU) over 14 months, and direct observation of episodes of care involving ten dyads of midwifery mentors and student midwife dyads. These observations were followed by individual semi structured interviews with participants. Setting: An alongside midwifery led unit in a Health Board in Wales, UK. This is an option for place of birth in the National Health Service in the UK. Sample: Ten dyads of midwifery mentors and student midwives. Findings: A conceptual framework emerged from the data in relation to the powerfully shared goals and ethos of the midwives working in this AMU. The framework gave shape and form to the particular nature of the teaching and learning experience in the midwifery led setting. The concept of a community of practice, firmly rooted in the authoritative knowledge and understanding of physiological birth, resulted in positive working practices and happy, motivated midwives who enhanced the birth experience for women. This supported the clinical and socially situated learning of student midwives and new colleagues through legitimate peripheral participation. Implications for practice, policy, education and research: Positive, committed and autonomous midwives make for a nurturing working environment and may therefore enhance the experience of birthing women. Midwives need to be able to work in an environment and community of practice which mirrors their own philosophy of care to promote professional wellbeing, and to develop the expert knowledge and skill in that area of practice over time.